Text Relationship dalam Jejaring Sosial di Kalangan Dewasa Muda (Studi Awal dengan Pendekatan Fenomenologis) - Andangsari, Esther Widhi (Humaniora, 2011)
This study is a preliminary study about social networking and text relationship among young adulthood. The purpose of this study is to get information or description about text relationship through social networking. Method of this study is qualitative method with phenomenology approach. The phenomenon of using social networking to build relationship with others is growing popular especially among young adulthood. Observing this phenomenon accurately, there is a changing in interaction pattern. It was a physically interaction or face to face interaction. But as growing popularity of technology or internet access, today interaction can do through online and without face to face interaction. Surprisingly, this online interaction and without face to face interaction is very popular at the present. From this preliminary study, the findings are social networking become a media to share emotion, opinion openly among people. Text relationship through social networking also need emotional setting which is substituted electronically and it is virtual emotional and not the real emotional. Social networking still give a chance to people to gather face to face, not only virtual gathering.